AB0004 Pharmacogenetic aspect of metotrexate, in a group of colombian patients with rheumatoid arthritis. (12th June 2018) - Saldarriaga, E.L.; González, C.A.; Restrepo, L.F.; Giraldo-Bustos, R.; Ballesteros-Muñoz, J.G.; Vásquez, A.Y.; Arias-Correal, S.; Valero, L.; Ospina, M.-J.; Lopez-Morales, P.; Couto-Luvie, E.; Soares-Santeugini, M.J.; et al.
Abstract : Background: Methotrexate (MTX) as monotherapy or in combination, is the most commonly Disease-Modifying-AntiRheumatic-Drug (DMARDs) used in rheumatoid arthritis (RA). About 40% of patients do not respond to treatment or have adverse effects. The genetic variability could be responsible for this phenomenon. Different studies suggest associations between polymorphisms in the enzymes involved in the metabolic pathway of MTX with alterations in the efficacy and toxicity. Objectives: Determine the polymorphisms of the enzymes involved in MTX metabolism in a group of Colombian patients. Methods: 400 patients with RA over 18 years old, diagnosed according to the ACR/EULAR classification criteria, who consecutively attended an outpatient RA clinic between March 2015 and December 2016 were included. MTX efficacy was defined by DAS28 score ≥3.2, liver toxicity by elevation of transaminases above three times the normal value, Haematological toxicity by: leukocytes<4, 000, Hb <9.5, platelets<150, 000, renal toxicity: creatinine >1.5. The single nucleotide polymorphisms (SNPs) studied were MTHFR C677T, MTHFR A1298C, ATIC C347G, RFC1 G80A, FPGS-AG and DHFR-CT and were identified by the technique of polymerase chain reaction in real time (RT-PCR). Results: The mean age of patients was 60.7±13.9 years, the duration of the disease was 13.2±10.9 years and 76% were women. A significant increase in the frequency of MTHFR C677T and A1298C SNPs (p=0.05 and p=0.048) were found in the responding patients compared to non-responders. The DHFR-CT and the ATIC C347G SNPs were significantly increased in patients with any toxicity to MTX (p=0.0095 and p=0.005 respectively). We did not find a significant difference between the polymorphisms studied with any specific toxicity. Conclusions: The Colombian population has similar statistical data compared to the global studies regarding the association of SPNs with the efficacy and toxicity of methotrexate, however the polymorphisms associated with inefficiency in the literature are not replicated in our data. These SNPs could be established as biomarkers to the methotrexate response in terms of efficacy and toxicity in our Colombian population with RA. Reference: [1] Fan H, Li Y, Zhang L, Li W. Lack of association between MTHFR A1298C polymorphism and outcome of methotrexate treatment in rheumatoid arthritis patients: Evidence from a systematic review and meta-analysis. Int J Rheum Dis2017;20(5):526–40. Disclosure of Interest: None declared